Pharmacokinetics of 400 mg Locally Infiltrated Ropivacaine After Total Knee Arthroplasty Without Perioperative Tourniquet Use. Issue 7 (1st October 2018) - Bakker, Sietske M.K.; Fenten, Maaike G.E.; Touw, Daan J.; van den Bemt, Bart J.F.; Heesterbeek, Petra J.C.; Scheffer, Gert-Jan; Stienstra, Rudolf
Abstract : Background and Objectives: Local infiltration analgesia (LIA) with ropivacaine for total knee arthroplasty (TKA) is increasingly used. Despite the high doses of ropivacaine, LIA is considered safe, and this perception is sustained by pharmacokinetic data demonstrating that maximum concentrations of ropivacaine stay well below the toxic threshold in plasma. These pharmacokinetic studies all involve TKA procedures with the use of a tourniquet. Recently, performing TKA without the use of a tourniquet is gaining popularity, but no pharmacokinetic data exist when LIA is administered for TKA without the use of a tourniquet. The purpose of this study was to describe the pharmacokinetic profile of a single-shot ropivacaine (200 mL 0.2%) and 0.75 mg epinephrine (1000 μg/mL) when used for LIA in patients for TKA without a tourniquet. Methods: In this prospective cohort study, 20 patients treated with LIA for TKA without a tourniquet were studied. Plasma samples were taken at 20, 40, 60, 90, 120, 240, 360, 480, 600, 720, and 1440 minutes after local anesthetic infiltration, in which total and unbound ropivacaine concentrations were determined. Results: Results are given as median (interquartile range [IQR]). Median peak ropivacaine concentration was 1.16 μg/mL (IQR, 0.46); median peak unbound ropivacaine concentration was 0.05 μg/mL (IQR, 0.02). The corresponding times to reach the maximum concentration for total and unbound ropivacaine were 360 (IQR, 240) and 360 (IQR, 360) minutes, respectively. Conclusions: Although great interindividual variability in ropivacaine concentration was found, both total and unbound maximum serum concentrations remained below the assumed systemic toxic thresholds in all samples. Clinical Trial Registration: This study was registered at Netherlands Trial Registry (http://www.trialregister.nl ), trial ID NTR6306.